The arbitrage In Securities Market Model And Some There Properties - Adel Murtda Al-awci; Noori F. Al-Mayahi (Al-Qadisiyah Journal of Pure Science, 2021)
The  applications of functional analysis in economics began worked out since the  by presenting theoretical studies related to the development and balance of financial  markets by building mathematical models with linear topological space , describing and defining the economic balance of the stock market in mathematical formulas and terms , and then using the theorems of  linear topological spaces such as Han's theorems . Banach , separation theorems  , open function theorem ,closed statement theorem and so on to create the necessary and sufficient condition to make the market model achieve viability , achieve no arbitrage , and not recognize No free Lunches